Correlation between surface PM2.5 and O3 in eastern China during 2015–2019: Spatiotemporal variations and meteorological impacts. (1st February 2023) - Wang, Lei; Zhao, Bingxue; Zhang, Yong; Hu, Hebing
Abstract: PM2.5 and ozone (O3 ) are two major air pollutants in China. A systematic evaluation of the spatiotemporal variations in the correlation between them is essential for their coordinated prevention and control. In this study, we investigated the spatiotemporal variations in the correlations between the surface PM2.5 and O3 concentrations, and the influences of the meteorological parameters in eastern China were analyzed. The major findings of this study are as follows. From 2015 to 2019, the annual number of PM2.5 (O3 ) pollution days in eastern China decreased (increased) by 8.6% (19.2%). In the three developed regions, the O3 concentrations increased with increasing PM2.5 when the PM2.5 concentrations were less than ∼50 μg m −3 ; while the O3 concentrations decreased with increasing PM2.5 when the PM2.5 concentrations were greater than ∼50 μg m −3, except in the Pearl River Delta. The daily average PM2.5 concentrations were positively correlated with the O3 concentrations in most regions and seasons in eastern China, but they were negatively correlated with the O3 concentrations in the cold season, especially in the NCP. The correlation between these two pollutants exhibited notable north-south and seasonal variations, and it tended to be more positively correlated as the PM2.5 concentration decreased. Further investigation revealed that the temperature was positively correlated with the O3 concentration, while they exhibited different seasonal variations with the PM2.5 concentration. The relative humidity was negatively correlated with the O3 concentration and positively correlated with the PM2.5 concentration in the NCP, but was negatively correlated with it in the YRD and PRD. The temperature was a significant meteorological parameter influencing the correlation between the PM2.5 and O3 concentrations, with a coefficient of determination ( R 2 ) of 0.83. Under high-temperature conditions, the PM2.5 and O3 concentrations exhibited a stronger positive correlation. These results provide guidance for coordinating PM2.5 and O3 pollution prevention and control in eastern China. Highlights: Correlation between PM2.5 and O3 exhibited notable north-south and seasonal variations. Correlation between PM2.5 and O3 tends to be more positive as PM2.5 decreased. Temperature was the key parameter influencing the correlation between PM2.5 and O3 .